Riconfigurare il trauma: rappresentazione, presentazione, testimonianza (Altre Modernità, 2022)
The essay examines the ways in which the work of art attempts to reconfigure traumatic experiences, affecting the dynamics with which they are inscribed in collective contexts. The creative processes of modelling offered by the work of art generate an effect of transgression that opens up a figural field in which trauma turns into an image and becomes visible. Three main strategies are investigated: representation, presentation and testimony. These are three different aesthetic modes of reconfiguring trauma that will be analyzed through artworks by Nelson Rangelosky, Teresa Margolles and Shilpa Gupta, presented during the 2019 Venice Art Biennale curated by Ralph Rugoff.
Keywords: Collective trauma; Memory; Figuration; Aesthetics